Eduardo Hopkins Rodríguez and viceregal Peruvian literature (1974-2020) - Sebastián Luna, Jaime (2024)
This article proposes a brief periodization of Eduardo Hopkins Rodríguez’s critical production on viceregal Peruvian literature. The bibliographical review is organised in four stages. From the formative stage (1974-1993), we highlight the use of rhetorical-stylistic analysis as an effort to overcome the prevailing biographicalism in contemporary criticism. We suggest that in the theoretical foundation stage (1994-2007) the author’s most outstanding contributions are developed: the revision of paratexts, which allows us to demonstrate a theoretical awareness of the Peruvian writer of the viceroyalty, as well as a defence of the interpretative openness of the texts in tune with an antiauthoritarian stance. The consolidation stage (2007-2015) is simultaneously shaped by the anthological work of his own critical production and a return to the rhetorical-stylistic bases. This return to the rhetorical-stylistic bases is present in his last stage, that of his latest publications (2015-2020).